URGENSI DEWAN SYARIAH NASIONAL (DSN) DALAM PEMBAHARUAN HUKUM EKONOMI DI INDONESIA - Halimatus Adiah (JURNAL CERDAS HUKUM, 2023)
Abstract The National Sharia Council (DSN) is the only institution or organization in Indonesia that is believed to be capable of issuing Islamic fatwa. Considering that technological, social and cultural development today is very rapid. Therefore, the existence of today's DSN can no longer be viewed with one eye, especially when it comes to provisions and fatwa related to Islamic khzana. Nevertheless, it is quite unfortunate that the fatwa funded by DSN have not all been absorbed by the government and formulated into regulation legislation. The implications are only those considered important that are accommodated and formulated into the Law, some of which are just ordinary fatwa. Where we know, that fatwa is not as coercive and binding as the Law. Nevertheless, the current existence of DSN has been taken into account, especially when it comes to contemporary banking and finance today. In conclusion, that the existence of DSN has enormous urgency in many ways and its urgency is not only for the Muslims themselves, but also for the benefit of the state. For this reason, credibility, idealism, honesty, and neutrality in giving birth to various fatwa products must uphold the values of honesty. So that the existence of this DSN can be a reference to all Islamic people, especially in Indonesia.